The cultural dimensions of collective action during environmental hazards: Assessing race, gender, and social support network dynamics in the Flint Water Crisis. (March 2023) - Shelton, Jenna L.; Chase, Elizabeth C.; Ajayi, Babatunde Patrick; Armstrong, Joyce; Ezell, Jerel M.
Abstract: Introduction: The water crisis in Flint, Michigan, a majority-Black, low-income city, consisted of citywide water contamination with lead (Pb) and various harmful bacteria, fracturing civic trust. Literature suggests that social networks form, or strengthen, in the absence of adequate government and institutional responses to environmental hazards. Nonetheless, little is known about how these networks are sociodemographically composed and how they may fuel collective action and drives certain health outcomes and beliefs. Methods: We conducted surveys with Flint residents, exploring differences in network dimensions based on dynamics including respondent demographics, the length of time to the respondent becoming cognizant of potential water contamination issues, and subsequent health outcomes and beliefs. Findings: Overall, the mean network size of respondents was 3.0 (±2.0) confidants. Irrespective of gender, Black respondents were more likely to have women in their network (p = 0.01). In general, women respondents had larger networks than men (p = 0.048), and individuals eligible for public benefits (e.g., Medicaid) had larger networks than those who were ineligible (p = 0.095). Blood lead level screening was higher among individuals with more women in their network, while increasing tie strength was associated with lower odds of depression/anxiety severity (PHQ-4) and PTSD (PTSD-PC-5) symptoms. Conclusions: Findings here suggest that social networks may have been important sources of support and information during the FWC. In particular, the presence of women in residents' social networks may have improved health promotion behaviors (screening) and lowered morbidity risks. These results highlight potential protective features of networks and the additive salience of gender following a socio-politically intricate environmental disaster.